EDUKASI KEMAMPUAN DIGITAL DAN PEMECAHAN KONTEN NEGATIF PADA ANAK SEKOLAH DASAR - Femilianita; Nurul Istiqamah Ishaq; Nurfadillah Apriliah; Reski Nurasmi; Andi Ardhila Wahyudi; Sukmawati (STKIP Subang, 2026)
The rapid development of digital technology has brought significant changes to the lives of elementary school–aged children, particularly in relation to the increasing use of gadgets that is not always accompanied by adequate digital literacy. Excessive and unsupervised gadget use can lead to various negative impacts, including decreased learning concentration, declining academic achievement, risks of digital addiction, exposure to negative content, and ethical issues in online interactions. This community service activity aimed to enhance elementary school students’ awareness and understanding of digital skills and negative content management through education on wise gadget use. The program was conducted at SD Inpres Sero, Makassar City, involving fifth- and sixth-grade students and teachers as partner participants, using a Participatory Action Research (PAR) approach. The methods included initial observation, interactive seminars, educational videos, quizzes, discussions, and evaluation. The results showed very high levels of student participation and enthusiasm, as well as an increase in students’ initial awareness of the importance of managing screen time, selecting safe and appropriate content, and applying digital ethics. This educational intervention proved effective in building a positive foundation of digital literacy despite being implemented within a limited time frame and with minimal resources. Overall, this activity confirms that a school-based educational approach oriented toward active student participation can serve as an adaptive alternative strategy for fostering healthy and responsible digital habits from an early age.